Teenagers and their Sexual Partners: What Age Difference Should Raise Concerns of Sexual Exploitation?. (3rd March 2020) - Cook, Louise; Mott, Alison
Abstract : Child sexual exploitation (CSE) is often characterised by a power imbalance between the abuser and the child. Age difference is one of the power imbalances observed. However, there is no clear guidance on what age difference should raise concern. This article provides empirical evidence on age difference observed between: (a) teenagers (13–17‐year‐olds) who have attended a sexual health clinic and their partners; and (b) teenagers who are already known to children's services owing to significant concerns of sexual exploitation and their partners. The findings provide recommendations on age cut‐offs that are more likely to be suggestive of the risk of CSE. The paper concludes that an age difference of four years or more for 13–16‐year‐olds and six years or more for 17‐year‐olds should alert professionals to the possibility of exploitation. Overall, about two per cent of teenagers seen in a general sexual health clinic population had partners meeting these age cut‐offs compared with 31.4 per cent of those for whom there were already significant CSE concerns. These age cut‐offs can support professionals, especially those with little or no experience or knowledge of CSE, to make an informed professional judgement. 'Provide[s] recommendations on age cut‐offs that are more likely to be suggestive of the risk of CSE' Key Practitioner Messages: A holistic approach to determining a young person's risk of sexual exploitation should include consideration of the age of the partner. Age 'cut‐offs' can help professionals decide what age difference should trigger concern and support decision‐making. We recommend age difference 'cut‐offs' of four years or more for 13–16‐year‐olds and six years or more for 17‐year‐olds.